2007
DOI: 10.1007/s00248-007-9264-8
|View full text |Cite
|
Sign up to set email alerts
|

Cultivable Bacterial Diversity of Alkaline Lonar Lake, India

Abstract: Aerobic, alkaliphilic bacteria were isolated and characterized from water and sediment samples collected in the winter season, January 2002 from alkaline Lonar lake, India, having pH 10.5. The total number of microorganisms in the sediment and water samples was found to be 10(2)-10(6) cfu g(-1) and 10(2)-10(4) cfu ml(-1), respectively. One hundred and ninety-six strains were isolated using different enrichment media. To study the bacterial diversity of Lonar lake and to select the bacterial strains for further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
85
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(107 citation statements)
references
References 34 publications
8
85
0
5
Order By: Relevance
“…Present study focused on the aerobic methylotrophs covering 1,100 km 2 of the Chilika Lake sediments through established molecular markers (such as the functional gene mxaF and phylogenetic 16S rRNA gene probes) which demonstrated the presence of phylogenetically diverse aerobic methylotrophs. The total viable counts were relatively higher in sediments near the sea mouth (S3; Panaspada) as also viewed by Joshi et al [44].…”
Section: Resultssupporting
confidence: 66%
“…Present study focused on the aerobic methylotrophs covering 1,100 km 2 of the Chilika Lake sediments through established molecular markers (such as the functional gene mxaF and phylogenetic 16S rRNA gene probes) which demonstrated the presence of phylogenetically diverse aerobic methylotrophs. The total viable counts were relatively higher in sediments near the sea mouth (S3; Panaspada) as also viewed by Joshi et al [44].…”
Section: Resultssupporting
confidence: 66%
“…Recently, the cultivation dependent and independent analyses of planktonic and sediment microbial communities include, among others, studying the soda lakes of South-East Siberia, Russia (Foti et al 2007(Foti et al , 2008, North-East Mongolia (Sorokin et al 2004), Inner Mongolia, China (Zhang et al 2001;Ma et al 2004a), Lonar Lake, India (Wani et al 2006;Joshi et al 2008), the East African Rift Valley, Kenya and Tanzania (Rees et al 2004;Mwirichia et al 2010Mwirichia et al , 2011, Wadi An Natrun, Egypt (Mesbah et al 2007), as well as Mono Lake, California, USA (Hollibaugh et al 2001;Humayoun et al 2003) and Soap Lake, Washington, USA (Dimitru et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A saline (NaCl B0.9%) and alkaline lake (pH B10) occupies most of the crater floor . Microbiological studies using culturedependent and -independent strategies have identified and characterized both bacterial (Kanekar et al, 1999Nilegaonkar et al, 2002;Wani et al, 2006;Joshi et al, 2008) and archaeal (Thakker and Ranade, 2002;Surakasi, 2007;Surakasi et al, 2007) communities in the Lonar Lake water and sediments. A culture-independent study that assessed archaeal diversity in the sediments reported that most of the retrieved euryarchaeotal sequences were related to methanogens (Wani et al, 2006).…”
Section: Introductionmentioning
confidence: 99%